Telesnoe prikosnovenie v sisteme sredstv pedagogiceskogo vozdejstvija trenera po chudožestvennoj gimnastike - Germanov, G. N.; Novikova, L. A.; Sekovanich, M. Yu.; Korolkov, A. N.; Strizhak, A. P. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
In the European method of sports training, the physical touch to children for purposes of correction of the movement or accentuated development of the motor abilities, is prohibited. In the Russian school of rhythmic gymnastics, the training without forced stretching, physical influence, tears and crying is not possible, though, not all parents can understand it, accept such methods of the education and upbringing and be allies of the trainer. What is it - necessary part of the training, method of the pedagogical support, or aggressive behavior of the teacher, invasion in personal space of the athlete, disrespect of rights of the child to personal integrity? In connection with the indicated problem, the aim of the scientific research is put forward: to study the opinion of the trainers, athletes, parents, and to establish permissibility of corrective physical actions of the trainer in relation to the child in development of flexibility, increase of mobility in joints and vertebral column, formation of posture, fixation of pose, correction of movement and training of these movements? On the agenda of the research the question is raised: whether there is interrelation between time expenses from the trainer for physical maintenance in techniques of the training and development of the children in the training process and rates of gain of the indicators of the physical and technical fitness of the young gymnasts?